O processo legislativo na Camara Municipal de São Paulo e a Constituição Federal de 1988 - Berardi, Luciana Andrea Accorsi (2006)
This labor intents to analyze the Legal Process of Sao Paulo s Municipal District in face to the 1988 Federal Constitution, whose concepts, regiment, principles, organization and performance date from the primordial of Brazilian structures, in parallel with the classical positivist doctrine. For the had of this premises, this study at first is probing the formation and evolution of the legal classic concepts of power, public opinion, sovereignty, democracy, representation and popular participation. It s boarding to, at a second, the factors which tempted to the duty and obligation of the State s discussion, the Brazilian Federation internal fragmentation through the distribution of distinct competences as one of the propulsive measures of the local development and incentive to the decision makers concerning to measures and course of peculiar public interest. It intends to present a brief boarding of the myth s ascension and its decay around the popular representation and participation, until achieving the constitutional position and how both are presented ahead the 1988 Constitution and the District of Sao Paulo s Organic Law. After a brief incursion on the concept and analysis of the Municipal Legislative Process, under the legal approach, it becomes a reflection on its procedure and formation, recurrent of the legislative office s exercise, always obeying the established Brazilian State principles: democratic, federative and republican, as established specifically in the constitutional law. Finally, we offer our conclusions and some considerations.